Exposure of home-attending healthcare workers to aerosolized medications (simulation study). (July 2019) - Elmashae, Yousef; Yermakov, Michael; Frank, Evan; Benjamin, Michael; Maier, Andrew; Newman, Nicholas; Reponen, Tiina; Grinshpun, Sergey A.
Abstract: Home-attending healthcare workers (HHCWs), one of the most rapidly growing occupations worldwide, are exposed to a wide range of aerosol contaminants, including pharmaceuticals administered to patients in their homes by nebulizer treatment. The aerosol concentration and exposure patterns may be vastly different from those identified in hospital environments. Inhalation exposure of healthcare professionals to nebulized medications has not been quantified. This pilot simulation study was conducted to measure particles released from a commercially available nebulizer-based aerosol delivery system into the indoor environment. Aerosolized medications such as Ipratropium Bromide, Budesonide, and Albuterol Sulfate (all suspended in a NaCl solution), and NaCl (used as medication to treat respiratory symptoms) were evaluated in individual trials. Deionized water was used as a control. The aerosols were measured using an Electrical Low Pressure Impactor at three locations of the HHCW-simulating manikin relative to the aerosol source. Exposure to all four selected aerosolized medications was significant (exceeding background control by one to four orders of magnitude). The particle size distributions measured for the four aerosols at a fixed distance from the source demonstrated similar trends with no significant differences identified in most cases. Although the total aerosol mass concentration in the breathing zone of the simulated HHCW ranged widely, from 2.29 to 10.2 μg/m 3, it was not significantly affected by medication type. Therefore, we concluded that NaCl can serve as a surrogate for assessing aerosol exposures, at least for the selected nebulizer-administered medications. Highlights: Simulated exposure of healthcare workers to nebulized medications was significant. The particle size distributions of four tested aerosolized medications were similar. No significant effect of medication on the total aerosol mass concentration was found. NaCl can serve as a surrogate for assessing aerosol exposures to the selected drugs.